Mediação didático-pedagógica no contexto da pandemia: desafios do trabalho docente nos anos iniciais do ensino fundamental - Oliveira, Jozelia Araujo (2023)
This research, entitled PEDAGOGICAL DIDACTIC MEDIATION IN THE CONTEXT OF THE PANDEMIC: CHALLENGES OF TEACHING WORK IN THE EARLY YEARS OF ELEMENTARY EDUCATION, has as its object of study the pedagogical didactic mediation from the perspective of teachers in the early years of Elementary School. It tries to na swer the question: how does the pedagogical didactic mediation carried out in the contexto femer gency remotete a chingre verberate in the construction processo freading and writing of children in the 1st, 2nd and 3rd years of Elementary School? The objective is tound erstand the implications of didactic pedagogical mediation in the initial process of construction of reading and writing, by students in the early years of elementary school, in the midst of emergency remotete aching in a municipal publics chool in Feira de Santana, Bahia. The research was basedon a qualitative descriptive approach (GIL 2008), see king tounder stand a social phenomenon in separable from its context basedon a single case study (GIL, 2009; YIN, 2015; LUDKE and ANDRÉ, 1986). Weopted for the case study, since case studie stend to portray reality in a more in-depthand complete way. For the production of data, the question naire, the interviews per agenda and theres earch diary wereused as research devices (GIL, 2009; HOLLY; ALTRICHTER, 2015; WELLER, 2006). The research collaborators are five teachers who worked during the pandemic period in classes of 1st, 2nd and 3rd years of elementary school at a municipal publics chool in Feira de Santana. As a technique for analyzing and processing data, Content Analysis, advocated by Bardin (2016), wasused. The researchs ought to contribute to there cords of narratives, which reveal challenges and impacts of pedagogical practices in the formation of beginnin greaders in a pandemic context. The research findings point out that pedagogical didactic mediation is essential in the initial language learning process, as well as demonstrating that the interruption of classes, distancing and lack of public policies that would guaranteeac cessand connectivity to the mostnee dy layerof the population reverberated in a negative effecton children's schooling in relation to learning writ tem language and reading.